2008
DOI: 10.1248/cpb.56.1555
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an Orally-Active Nonsteroidal Androgen Receptor Pure Antagonist and the Structure-Activity Relationships of Its Derivatives

Abstract: The 3-(4-cyano-3-trifluoromethylphenyl)-5,5-dimethylthiohydantoin derivatives which have carboxy-terminal side chains were synthesized and their agonistic/antagonistic activities against androgen receptor (AR) measured. Among them, compound 13b showed antagonistic activity (IC 50 ‫031؍‬ nM) with no agonistic activity even at 10000 nM. This compound exhibited significant metabolic stability and oral antiandrogenic activity (ED 50 ‫؍‬ 7 mg/kg).Key words androgen receptor; pure antagonist; prostate cancer Chem. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…To elucidate the pure AR antagonistic nature of CH5137291 in terms of three-dimensional structure, a docking model analysis was performed. The folding of helix 12 of AR is reported to be caused by ligand binding and is considered necessary for a ligand-induced AR agonist effect (39,40). The docking model revealed that CH5137291 intensively collided with the M895 residue of helix 12 in both wild-type AR and W741C-mutant AR (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To elucidate the pure AR antagonistic nature of CH5137291 in terms of three-dimensional structure, a docking model analysis was performed. The folding of helix 12 of AR is reported to be caused by ligand binding and is considered necessary for a ligand-induced AR agonist effect (39,40). The docking model revealed that CH5137291 intensively collided with the M895 residue of helix 12 in both wild-type AR and W741C-mutant AR (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The folding of helix 12, present in the ligand-binding domain of AR, is reported to be necessary for a ligand-induced agonist effect on AR transcriptional activity (39,40). The crystal structure of the bicalutamide/ W741C-mutant AR complex revealed that bicalutamide does not collide with the C741 of the AR as it does with W741 in the wild-type AR; therefore, helix 12 of the bicalutamide/W741Cmutant AR complex is folded in the same manner as when a ligand, such as R1881, binds to it (Fig.…”
Section: Complete Inhibition Of Helix 12 Folding By Ch5137291 In Wildmentioning
confidence: 99%
“…17 However, phenyl sulfonamide derivatives 11a and 11b tended to show weaker activities in vivo than CH4933468. Since these compounds were metabolically stable in human liver microsome and showed acceptable permeability in a parallel artificial membrane permeation assay (PAMPA), weak in vivo antiandrogenic activities might be mainly attributed to low solubility.…”
Section: Resultsmentioning
confidence: 97%
“…The thiohydantoin derivative with a carboxyl terminal side chain showed that pure antagonistic activities in vitro and oral AR antagonistic activity in vivo [37]. In this work, the molecular modeling, molecular docking and ADMET of 16 compounds of 5,5-dimethylthiohydantoin derivatives, which synthesized by [38] were conducted for the treatment of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%